UV-Irradiation Effect on PC/DOP Composite in the C=C Region - Yousif, R. H. (Iraqi Journal of Physics, 2002)
In this research we study the effect of UV radiation on pure PC samples and doped samples with plasticizer (DOP) for different exposure times (6, 12, 18, 24h). The study have been made on the change in the IR spectra causes by the UV radiation on both kinds of samples, besides the morphology changes were also studied by the optical microscope. From the results we conclude that the increasing of exposure causes the elaboration of CO2 and C2 gases.